2018
DOI: 10.6027/tn2018-549
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Fuel Oil (HFO)

Abstract: Third-party content: The Nordic Council of Ministers does not necessarily own every single part of this work. The Nordic Council of Ministers cannot, therefore, guarantee that the reuse of third-party content does not infringe the copyright of the third party. If you wish to reuse any third-party content, you bear the risks associated with any such rights violations. You are responsible for determining whether there is a need to obtain permission for the use of third-party content, and if so, for obtaining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The chemical and physical properties of HFO depend not only on its origin, quality, and properties but also on the distillate variations added during the viscosity adjustments in the refinery process [4] . Based on the concentration of sulfur (S), HFO is classified as high‐, medium‐ or low‐S fuel oil with typical chemical composition shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical and physical properties of HFO depend not only on its origin, quality, and properties but also on the distillate variations added during the viscosity adjustments in the refinery process [4] . Based on the concentration of sulfur (S), HFO is classified as high‐, medium‐ or low‐S fuel oil with typical chemical composition shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms 2023, 15, x FOR PEER REVIEW 14 of 17 units with a high ramp capacity contribute less in terms of GHG emissions than they do in terms of energy consumption. They offer cleaner conversion with poor combustion indices [38]. Table 4 lists the CO2 emission coefficients of the assessed generators in relation to their fuel type [29].…”
Section: Prospects For Real-world Conditionsmentioning
confidence: 99%
“…These features also cause HFO to persist longer in the marine environment and travel further. The thickness of HFO slicks range from 0.5 to 1.0 cm, in contrast to crude oil, which can vary from 1 to 5 mm (Fritt-Rasmussen et al 2018). (The lighterweight and more volatile components of crude oil have slick thicknesses of <1 mm).…”
Section: Differences Among Crude Oil Hfo and Alternative Fuelsmentioning
confidence: 99%
“…Studies examining the effectiveness of spill recovery technologies and methods have shown that mechanical recovery mechanisms (booms) are the most effective means of containment (Fritt-Rasmussen et al 2018). In situ burning is not effective because of the lack of light (volatile and flammable) hydrocarbon compounds and the suspension of much of the HFO mass in the water column.…”
Section: Differences Among Crude Oil Hfo and Alternative Fuelsmentioning
confidence: 99%